PERBANDINGAN KONSEP KEPRIBADIAN MENURUT BARAT DAN ISLAM - Agus Silahudin (Program Pascasarjana Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
Personality is something that attracts the attention of many parties. Many theories that try to give some concepts and definitions related to the human personality with different points of view. Western psychologists try to provide a definition of personality that is psychological based on the word person, but until now the personality psychologists themselves still do not agree on what the definition of personality actually is. While in Islam, the concept of personality has been thoroughly discussed in various Islamic literature. The Apostle as an example for Muslims has applied the concept of personality and actions and behavior. Thus, the concept of personality according to Islam, that Islamic personality is defined as